An eLearning module is comparable to face-to-face teaching in a nursing human pathophysiology subject - Donkin, Rebecca; Hatje, Eva; Reinke, Nicole B. (Nurse education today, 2022)
Human pathophysiology is important in undergraduate nursing education to help students develop clinical reasoning skills. Traditionally pathophysiology education in undergraduate nursing is taught face-to-face. However, eLearning in nursing curricula may provide flexible delivery options. With increased inclusion of technology enhanced learning in nursing curricula, a hematology eLearning module was evaluated in a pathophysiology subject to determine whether it was comparable to face-to-face learning. Single-blind randomized pre-test/post-test controlled trial. School of Health and Behavioural Sciences, University of the Sunshine Coast. A total of 271 second-year undergraduate students enrolled in Human Pathophysiology were included in the study. Students were from three bachelor programs: Nursing Science; Paramedic Science; and Clinical Exercise Physiology. Students were randomly allocated to either the experimental group (n = 85) or the control group (n = 186). A hematology eLearning module was designed to be self-directed and learner-centered, guided by constructivist learning theories for delivery in the human pathophysiology subject. The experimental “eLearning” group completed the module independently, and the control “face-to-face” group completed equivalent paper-based activities facilitated by a tutor. All students completed a pre-test assessment and two post-test assessments two weeks after the intervention and at the end of the subject. There was no significant difference in assessment scores between the experimental and control groups, or between nursing and other programs. eLearning was comparable to face-to-face teaching in this study. We recommend further research to strengthen the links between pathophysiology theory to clinical reasoning skills using eLearning. •eLearning can be a comparable mode to face-to-face learning for nursing students.•Technology enhanced learning, and specifically eLearning, requires consideration of learning theories to guide nursing curriculum design.•Nursing academics need time and expert skills to develop technology enhanced learning content.